Trait, SNP ID, allele, chromosome, position, model, QTN effect, LOD score, proportion of phenotypic variation explained (r2), and minor allele frequency of the most significant single nucleotide polymorphisms (SNPs) for BNF-related traits measured on cowpea mini core population evaluated in the screen house at MUARIK, Uganda. - Gelase Nkurunziza (21300313) (2025)
Trait, SNP ID, allele, chromosome, position, model, QTN effect, LOD score, proportion of phenotypic variation explained (r2), and minor allele frequency of the most significant single nucleotide polymorphisms (SNPs) for BNF-related traits measured on cowpea mini core population evaluated in the screen house at MUARIK, Uganda.